Find No. 1 value of expression: 1)-42+75+(-14)+ (-26)+56 2) 12+(-20) - (-11)-(-6)-10 3)3 5/12-(-1 1/3)+ (-4 3/8) No. 2 Simplify expression and find its value if b = 3 4/9 - 13.24+b+4.9+8.24+ (-4.9)

158
1.-42+75+(-14)+ (-26)+56 = - 42+75-14-26+56=(75+56)-(42+14+26)=131 - 82=49 12+ (-20) - (-11)-(-6)-10=12-20+11+6-10=(12+11+6)-(20+10)=29-30 = - 1 3 5/12 - (-1 1/3)+ (-4 3/8)=3 5/12+1 1/3 - 4 3/8=3 10/24+1 8/24 - 4 9/24=9/24=3/8 2.-13.24+ in +4.9+8.24+ (-4.9) =-13.24+ in +4.9+8.24 - 4.9= in - 5 at in =3 4/9 3 4/9 - 5 = - (5-3 4/9) = - (4 9/9 - 3 4/9) = - 1 5/9
149
Answer add